The Impact of Covid-19 on Online Learning in Grade 2 Elementary School Students: Dampak Covid-19 Terhadap Pembelajaran Online Pada Siswa Kelas 2 Sekolah Dasar - Hidayati, Ucik; Rezania, Vanda (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the impact of covid-19 on the online learning for second grade students at SDN Cemengkalang.. This study uses a descriptive qualitative approach. The subjects of this study were principals, teachers, and students at SDN Cemengkalang. This study uses data collection techniques in the form of observation, interviews, and documentation. Data analysis used steps of data reduction, data presentation, and drawing conclusions. Data validity using triangulation of data sources and techniques. The results of the study indicate that it can be seen that the real impact of the emergence of the covid-19 outbreak on teaching and learning activities for elementary school students is a shift in the learning process from initially doing face-to-face learning at school. teachers and other peers for distance learning, relying on technology and the internet available in every student's home without having to meet face-to-face with teachers and other students. The Covid-19 outbreak has had a major impact on aspects, both economic, social, cultural, especially in the field of education. In this case, character education must also coexist with the media used in online learning in accordance with the provisions of each subject and school teacher.